Learning Motivation of Children: Viewed from the Socio-Economic Aspect - Dwirianto, Sabarno; Sri Wahyuni (Universitas Lancang Kuning, 2022)
The poverty rate of Pekanbaru city increases every year. As a result, the dropout rate is increasing. Students experience a decrease in the value of learning outcomes due to helping parents at work. This results in students being less motivated to go to school due to the socio-economic demands of their peers at school. The tendency of students who come from poor families to have a low assessment of their happiness in life (subjective welfare). This study aims to describe the learning motivation of students who come from poor families and how the implications of counseling services in increasing the learning motivation of children who come from poor families. This study uses a descriptive quantitative approach. The population of the study was students from children who received assistance from poor students in 2015 with a sample of 152 students, who were selected by using multistage random sampling technique. The instrument used is a scale of student motivation from poor and reliable families with Cronbach's Alpha value of 0.923. Data were analyzed by descriptive statistics. The research findings show that students' learning motivation is in the high category. Based on the research findings, there are several implications for guidance and counseling services in schools, namely: Information Services, Content Mastery Services, Individual Counseling Services, Group Guidance Services and Group Counseling Services.